Proliferative Index and Microvessel Density as Potential Prognostic Markers of Canine Oral Malignant Melanomas - Choisunirachon, Nan; Tanaka, Yuiko; Saeki, Kohei; Sasaki, Nobuo; Nishimura, Ryohei; Nakagawa, Takayuki (The Thai Journal of Veterinary Medicine, 2014)
Several reports have indicated the prognostic significance of the proliferative index (PI) and microvessel density (MVD) in canine oral malignant melanomas (MM). However, a correlation between the PI and MVD of oral MM in dogs has never been elucidated. Here, we evaluated the expression of Ki-67 and CD31 using double immunofluorescence staining to investigate the correlation of PI with MVD in 37 spontaneous canine oral MMs. No correlation was found between the MVD and PI values or between those and any clinicopathologic findings. However, a correlation was found between the PI value and both clinical stage (p = 0.0453) and degree of tumour pigmentation (p = 0.0431). Further, the PI significantly correlated with the survival period of canine oral MM patients (p = 0.0209). The results of our study suggested that no relationship existed between the PI and MVD of canine oral MMs, and that the PI was a more reliable prognostic marker for canine oral MMs than MVD.